The Formulation of a New Class of Three-Dimensional Invariants of Legendre and Tchebichef Moments - Ong, Lee Yeng (2008)
This thesis introduces three-dimensional invariants of orthogonal moments, which are Legendre and Tchebichef. During implementation, Legendre moments are defined in continuous domain, which needs to undergo discrete approximation. Meanwhile, the Tchebichef polynomials that have close relationship with Legendre polynomials are directly stated in diecrese form.